Constitutive centromere-associated network contacts confer differential stability on CENP-A nucleosomes in vitro and in the cell - Cao, Shengya (Mol Biol Cell, 2018)
Eukaryotic centromeres are defined by the presence of nucleosomes containing the histone H3 variant, centromere protein A (CENP-A). Once incorporated at centromeres, CENP-A nucleosomes are remarkably stable, exhibiting no detectable loss or exchange over many cell cycles. It is currently unclear whether this stability is an intrinsic property of CENP-A containing chromatin or whether it arises from proteins that specifically associate with CENP-A chromatin. Two proteins, CENP-C and CENP-N, are known to bind CENP-A human nucleosomes directly. Here we test the hypothesis that CENP-C or CENP-N stabilize CENP-A nucleosomes in vitro and in living cells. We show that CENP-N stabilizes CENP-A nucleosomes alone and additively with CENP-C in vitro. However, removal of CENP-C and CENP-N from cells, or mutating CENP-A so that it no longer interacts with CENP-C or CENP-N, had no effect on centromeric CENP-A stability in vivo. Thus, the stability of CENP-A nucleosomes in chromatin does not arise solely from its interactions with CENP-C or CENP-N.